The discovery of islands : essays in British history - Pocock, J. G. A. (John Greville Agard), 1924- (Cambridge University Press, 2005)
The Discovery of Islands presents a series of linked essays by one of the world's leading historians. Each essay presents British history as that of several nations interacting with an imperial state, a view which has been hugely influential in recent studies.